2011
DOI: 10.2139/ssrn.3170961
|View full text |Cite
|
Sign up to set email alerts
|

On the Design of Education Conditional Cash Transfer Programs and Non-Education Outcomes: The Case of Teenage Pregnancy

Abstract: We investigate the effect of education Conditional Cash Transfer programs (CCTs) on teenage pregnancy. Our main concern is with how the size and sign of the effect may depend on the design of the program. Using a simple model we show that an education CCT that conditions renewal on school performance reduces teenage pregnancy; the program can increase teenage pregnancy if it does not condition on school performance. Then, using an original data base, we estimate the causal impact on teenage pregnancy of two ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Another set of comparative studies explored whether the conditions established within the CCT programs can explain the variations in adolescent pregnancy. One of these studies explored the impact of different conditions of CCTs implemented in Bogotá, Colombia ( 25 ), where one policy conditioned certain benefits to the completion of high school while the other did not. Using a representative survey, the study authors found that school performance requirements had a positive effect on reduced teenage pregnancy, versus attendance requirements alone, which had no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Another set of comparative studies explored whether the conditions established within the CCT programs can explain the variations in adolescent pregnancy. One of these studies explored the impact of different conditions of CCTs implemented in Bogotá, Colombia ( 25 ), where one policy conditioned certain benefits to the completion of high school while the other did not. Using a representative survey, the study authors found that school performance requirements had a positive effect on reduced teenage pregnancy, versus attendance requirements alone, which had no effect.…”
Section: Resultsmentioning
confidence: 99%